From funding to financing: perspectives shaping a research agenda for investment in urban climate adaptation. Issue 3 (2nd September 2019) - Keenan, Jesse M.; Chu, Eric; Peterson, Jacqueline
ABSTRACT: There is growing recognition of the importance of funding and financing arrangements to enable climate change adaptation in cities. However, there has been little critical analysis into the underwriting and governance mechanisms necessary support broader scaled application. Through surveying recent literature, this article offers conceptual clarity for understanding emerging adaptation finance mechanisms that intersect with urban governance, planning, and management functions. The article assesses two key conceptual domains: (i) the distinction between adaptation funding and financing and (ii) the synergies, conflicts, and trade-offs associated with mobilizing adaptation investments in the private sector. The article argues that a clearer delineation of these two domains will clarify the objectives, mechanisms, and larger governance implications of investment in urban adaptation. This article provides a roadmap for future scholarly inquiries that may advance the conceptual and analytical discipline necessary to evaluate the feasibility and desirability of investments from often-conflicting perspectives, interests, and actors.